Implementation of Knowledge Management in Higher Education: A Comparative Study of Private and Government Universities in India and Abroad - Galgotia, Dhruv; Lakshmi, Nirupa (Frontiers in Psychology, 2022)
All academic institution contributes to the corpus of knowledge in some way. To keep expanding, the resulting information and data must be collected in a single area and shared throughout society. Knowledge developed in academic institutions is not adequately preserved or gathered, according to research. It has also been observed that the majority of the content or knowledge developed in academic institutes is unknown to the general public and is categorized as a literature review, which may be useful if proper coding is kept in the organization. The purposeful integration of humans, processes, and technology dedicated to developing, capturing, and executing an organization's creative infrastructure is known as a Knowledge Management (KM) method. Knowledge Management supports educational institutes in refining their capability to acquire and share information and knowledge, applying it to problem resolution and promoting research and continuous development. This paper advocates a holistic strategy for finding, analysing, recording, retrieving, and distributing the whole of an administration's data properties. Databases, records, procedures, regulations and hitherto un-captured knowledge and talent in ordinary employees are samples of these properties. Higher education institutions can use KM as a tried and true approach to dealing with their problems. KM aids in the motivation of research as well as the promotion of partnerships and innovations in the future.